Option-Games Analysis on Strategic Partnership for an Innovative High- Tech Energy Industry of the Smart Houses: Targeting at Optimizing between Flexibility and Commitment Values - Nyein Aye, Nyein; Fujiwara, Takao (Technology Transfer and Entrepreneurship (Discontinued), 2017)
Energy has been a key in the progress of human society. In order to meet the increase in energy demand in the 21st Century, efficient and effective management of energy resources and innovative technology for producing it is inevitable and has become very crucial. Focusing on the Japanese pioneering Smart House case, I would like to search the potential of new energy industry for the regional development and ecological sustainability in Myanmar. This paper will help us in examining a possibility of option-games for optimizing total firms’ values between flexibility and commitment in founding the strategic partnerships as an industrial cluster formation. And in this paper, by analyzing the situation of two firms in a joint research venture for the Smart House, we find that a pioneer can create win-win relationship with a follower or a rival to recover its irreversible investment, to some extent, through the sharing strategy.
Keywords: regional development